Characterizing Middle Grade Students’ Integrated Alternative Science Knowledge about the Effects of Climate Change - Sarah Jennings Fick; Nancy Butler Songer (Journal of Education in Science, Environment and Health)
Recent reforms emphasize a shift in how students should learn and demonstrate knowledge of science. These reforms call for students to learn content knowledge using science and engineering practices, creating integrated science knowledge. While there is existing literature about the development of integrated science knowledge assessments, few studies examine the character of alternative integrated science knowledge (AISK) that students demonstrate when responding to these assessment items. This study describes the AISK middle grade students demonstrate in response to integrated science tasks. Students completed a pre-instruction task by making predictions, justifying their predictions about the geographic range of species’ habitats, and adjusting that prediction based on a climate change scenario.These findings revealed four areas of AISK: 1) Climate Data Interpretation and Analysis, 2) Identifying Climate Patterns, 3) Identifying Causes of Climate Patterns, and 4) Justifying Climate Claims. For each area, specific patterns in AISK were identified and described. The findings indicate that integrated assessments can provide insights into students’ struggles coordinating science content and practices for integrated knowledge products, and present a continuum to which students’ AISK can be compared. This work has potential to be used for the development of teaching strategies to support students’ developing integrated science knowledge.